Asia's emergence as the world's economy power center - consequencies for competitiveness of the EU (lessons, risk and challenges) - Baláž, Peter
Zmeny vo vývoji globálnej ekonomiky a nová pozícia Číny. Základné atribúty konkurencieschopnosti EÚ voči ázijským rivalom.